Orphan medicines: a success with a challenging future. (March 2013) - Saint-Raymond, Agnes; Llinares, Jordi
<x xml:space="preserve">Abstract</x> The implementation of the European Union (EU) Regulation for orphan medicines has resulted in > 1000 designations and > 70 marketing authorisations. Of those, in 21 cases (27%) the orphan medicine was the first authorised in that disease. The number of designations is increasing by approximately 7% per year. In parallel, the awareness on rare diseases has increased across the EU with the establishment of research networks. Recently, the International Rare Diseases Research Consortium (IRDIRC) has been established, aimed at facilitating and coordinating research in rare diseases internationally. There is mounting pressure on health reimbursement systems for expensive medicines. The fragmentation of frequent diseases into multiple subsets clashes with the current designation criteria and draws on the limited incentives available. These are two of the biggest risks to the current system. The societal benefit of developing medicines for rare diseases, both in terms of social justice and scientific added value is an enormous opportunity for advancing development of successful treatments. In Europe, regulators are engaged in moving towards close collaboration with health technology assessment bodies to address those problems affecting orphan drugs and ensuring society benefits from drug development in this area.